2002
DOI: 10.1073/pnas.212527599
|View full text |Cite
|
Sign up to set email alerts
|

The genome sequence of Bifidobacterium longum reflects its adaptation to the human gastrointestinal tract

Abstract: Bifidobacteria are Gram-positive prokaryotes that naturally colonize the human gastrointestinal tract (GIT) and vagina. Although not numerically dominant in the complex intestinal microflora, they are considered as key commensals that promote a healthy GIT. We determined the 2.26-Mb genome sequence of an infant-derived strain of Bifidobacterium longum, and identified 1,730 possible coding sequences organized in a 60%-GC circular chromosome. Bioinformatic analysis revealed several physiological traits that coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
796
7

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 873 publications
(848 citation statements)
references
References 48 publications
19
796
7
Order By: Relevance
“…A protein sequence comparison showed that this sequence was homologous to the N-terminal amino acid sequences of the BSH enzymes from many enteric bacteria, with the highest identity to that of the B. longum BSH enzyme (42,48). Only one difference between the amino acids, Thr 13 of B. longum BSH and Met 13 from B. bifidum BSH, was found.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…A protein sequence comparison showed that this sequence was homologous to the N-terminal amino acid sequences of the BSH enzymes from many enteric bacteria, with the highest identity to that of the B. longum BSH enzyme (42,48). Only one difference between the amino acids, Thr 13 of B. longum BSH and Met 13 from B. bifidum BSH, was found.…”
Section: Resultsmentioning
confidence: 91%
“…The importance of the SH group in the N-terminal cysteine was confirmed by the fact that replacing Cys with other (42,48). The predicted ORF of 951 bp displayed 83% DNA sequence identity and 95% deduced amino acid sequence similarity to BSH from B. longum NCC 2705 (42). Such a discrepancy is due to different codon usage, mostly at the third position.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The number of surface-associated proteins in B. longum was predicted through a bioinformatic analysis using dedicated software (Table 1), taking into account the genome annotation of B. longum NCC 2705 (Schell et al, 2002). The results of the different location predictions were combined by grouping the proteins into classes according to signal peptides for export features (145 proteins), at least one hypothetical transmembrane segment (361 proteins), proteins anchored covalently to the peptidoglycan (LPXTG sorting signal; 13 proteins) or to the membrane (lipoprotein motifs; 25 proteins), and proteins which are noncovalently bound to the surface (8 proteins).…”
Section: Resultsmentioning
confidence: 99%
“…HF/carbohydratefree diet). Analysis of the genome sequence of Bifidobacterium longum reveals that bifidobacteria possess long-chain fatty acyl-coenzyme A synthetases that may play a role in fatty acid utilization (Schell et al, 2002). Thus the potential ability of Bifidobacterium spp.…”
Section: Discussionmentioning
confidence: 99%